Quality Parameters of Plum Orchard Subjected to Conventional and Ecological Management Systems in Temperate Production Area - Mariana Rusu; Irina-Gabriela Cara; Florina Stoica; Denis Țopa; Gerard Jităreanu (Horticulturae)
Environmental protection, global food security, and nutritional quality are critical issues for worldwide sustainable development. Plums (Prunus domestica L.), well-known for their rich nutritional content and distinct phytochemical profile, have received increased attention due to their potential health benefits. The present study evaluates the ecological and conventional management systems of quality parameters in three plum varieties—Tuleu Gras, Record, and Centenar—and establishes suitable practices to improve fruit quality and yields. The fruit morphometric features (color, firmness, soluble solid content, titratable acidity, and total sugar) were analyzed during their raw fruit state, while different fruit-sample extracts were assessed for phytochemical compounds and heavy metal concentrations, specifically, zinc, copper, nickel, and cadmium. The results show a wide variability in the examined characteristics among management practices that differentially accumulated throughout the ripening phase and significantly influenced the nutritional value of the plum fruit. The application of an ecological management practice yielded small plum fruits (38 g) and maintained a more consistent and vigorous fruit color compared with the conventional system (83 g). Moreover, ecological plums have higher antioxidant activities, total polyphenols, and flavonoids (21.70–25.54 µM Trolox/g of dw, 3.89–7.76 mg GAE/ g of dw, and 1.45–3.65 mg CE/g of dw, respectively). Among the content of metals in the plum fruit, copper exhibited the highest concentrations (0.83–1.21 mg/kg), while cadmium was detected at the lowest levels (0.006–0.009 mg/kg). The potential health implications of heavy metals, by calculating their estimated daily intake (EDI), target hazard quotient (THQ), and hazard index (HI), for both adults and children were also analyzed. The EDI values of accumulated elements in the plum fruits followed the order of Cu > Zn > Ni > Cd with no concern for human health (THQ and HI < 1). According to this study’s findings, fruit quality parameters are significantly higher in ecological plums, providing a compelling argument for adopting sustainable agricultural practices. These results highlight the importance of selecting sustainable agricultural practices, not only to safeguard the environment but also to ensure high-quality products suitable for human consumption.